Can Indian Millennials be Engaged Through Online Customer Gamified Experience? - Srivastava, Mallika; Fernandes, Semila (Indian Journal of Marketing, 2022)
Purpose: Extant literature has indicated that millennials in emerging markets could not trust the brand. Hence, companies should be able to build the correct type of trust and experiences to create a gamified experience, resulting in brand loyalty. This paper attempted to establish the relationships among online gamification experience, customer brand engagement, online engagement intention, and brand loyalty in India's developing economy. Methodology: We conducted a self-administered web-based questionnaire-based study among Indian millennials between February and April 2020. The study applied SEM to explore the proposed association in the structural equation path model. Findings: The current study confirmed that the gamification experience among the Indian millennials had a significant favorable influence on millennials' continued engagement intention, which positively impacted customer brand engagement and brand loyalty. The gameful experience was positively related to continued engagement intention. Continued engagement intention and customer brand engagement were also positively correlated. Moreover, customer brand engagement was positively associated with brand loyalty. However, the gamified experience had a negative association with customer brand engagement. Originality: The study positioned the role of online-gamified experience amongst Indian millennials towards brand engagement.